let us be responsible the three milk bottles more stories - hassan, afaf mohamed (egypt dar almostakbl, 2020)
as the morals and values of kids arw determined at an early age, we bring 'let us be' series for your tiny-tots that will help bulid their values and chahacters. with cute and cuddly animals characters, these stories help teach kids how to lead a meaningful life by being honest, responsible, truthful and caring human being
english stories
For children from 3 to 6 years old
11
Keywords: english stories